Descriptive Study Of The Incidence Of Preeclampsy In Pregnant Women At Ajibarang II Health Center - Elisa Ulfiana; Khobibah Khobibah; Ida Farida (Journal of Midwifery Science: Basic and Applied Research, 2023)
Preeclampsia is a specific condition in pregnancy characterized by placental dysfunction and a maternal response to systemic inflammation with endothelial activation and coagulation (POGI, 2016). Preeclampsia is called a "disease of theory", because there is no theory that can clearly explain the risk factors for this disease. The purpose of this study was to describe the incidence of preeclampsia in pregnant women at the Ajibarang II Health Center. The factors studied were age, education level, parity, body mass index (BMI), and preeclampsia category. This study used a quantitative research type with a descriptive survey design method using a retrospective approach based on medical record data. The population is pregnant women who carry out examinations in January 2019 - December 2021. The sampling technique uses total sampling with a sample of 130 respondents in the form of pregnant women with preeclampsia. The results showed that the majority of respondents based on age in the 20-35 year age category were 80 respondents (61.5), based on education level namely Junior High School (SMP) as many as 46 respondents (35.4%), based on parity namely Multipara as 91 respondents (70.0%), based on Body Mass Index (BMI), that is, 69 respondents (53.1%) are overweight, based on the preeclampsia category, namely mild preeclampsia, there are 114 respondents (12.3%). Research suggestions, it is hoped that pregnant women can pay more attention to risk factors that can occur and health service workers improve in providing counseling